1998
DOI: 10.1001/archderm.134.9.1075
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Clinical Criteria for Diagnosis of Bullous Pemphigoid

Abstract: To check the potential usefulness of clinical criteria for the diagnosis of bullous pemphigoid when state-of-the-art techniques such as Western immunoblotting, immunoprecipitation, and indirect immunofluorescence on salt-split skin or direct immunoelectron microscopy are not available.Design: Comparison of the clinical criteria between 2 groups (with and without bullous pemphigoid) as defined by immunoelectron microscopy used as standard criterion, in a prospective study. Multivariate logistic regression analy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
132
3
7

Year Published

1998
1998
2017
2017

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 171 publications
(143 citation statements)
references
References 48 publications
1
132
3
7
Order By: Relevance
“…bullous pemphigoid (BP) represents the most common cutaneous subepidermal bullous autoimmune disorder. [1][2][3] The disease typically presents in elderly patients with a generalized bullous eruption and, more rarely, mucous membrane involvement. 4,5 Bullous pemphigoid is potentially associated with substantial morbidity.…”
Section: Discussionmentioning
confidence: 99%
“…bullous pemphigoid (BP) represents the most common cutaneous subepidermal bullous autoimmune disorder. [1][2][3] The disease typically presents in elderly patients with a generalized bullous eruption and, more rarely, mucous membrane involvement. 4,5 Bullous pemphigoid is potentially associated with substantial morbidity.…”
Section: Discussionmentioning
confidence: 99%
“…It mainly occurs in the elderly. Recent European studies reported that a significant proportion of BP patients were in poor general condition and had a poor prognosis [1,2,3,4,5,6]. Neurological disorders such as dementia occurs frequently in the elderly [7].…”
Section: Introductionmentioning
confidence: 99%
“…We have previously proposed a set of 4 criteria for the diagnosis of BP, including absence of atrophic scars, absence of predominant head and neck involvement, absence of mucosal involvement and age above 70 years [27]. We found that the diagnosis of BP could be made with a sensitivity of 90% and a specificity of 83% if patients had 3 of these 4 criteria [27].…”
Section: Introductionmentioning
confidence: 99%